The full management from first-line to third-line treatments in patients with Her-2–negative advanced gastric cancer - Chang, Chunxiao; Pei, Yanqing; Xu, Jun; Zhang, Wenyu; Zhang, Jianbo; Shi, Shengbin (Frontiers in Oncology, 2022)
Background The aim of this study was to evaluate retrospectively the efficacy of full management from first-line to third-line treatment in advanced gastric cancer (GC) with Her-2 negative patients. Methods The efficacy and survival time of a total of 126 patients who received first-line treatment with oxaliplatin plus fluoropyrimidine (S-1 or capecitabine or fluorouracil), second-line treatment with nab-paclitaxel, and third-line treatment of immune-checkpoint inhibitors between September 2019 to December 2021 were analyzed. Results Forty-two, 36, and 48 patients received CapeOX, FOLFOX, and SOX as first-line treatment. All patients received nab-paclitaxel alone as a second-line treatment. Thirty-one, 56, and 39 patients received nivolumab, sintilimab, tislelizumab as third-line treatment. The median PFS1, median PFS2, and median PFS3 was 6.9 months (95% confidence interval [CI], 6.8–7.4), 5.5 months (95% CI, 5.3–5.7), and 3.5 months (95% CI, 3.4–3.7). The median PFS3 was 3.8 months (95 % CI, 3.3–4.2) and 3.5 months (95 % CI, 3.3–3.7) among the EBV-positive and EBV-negative, respectively (P=0.09). In addition, the median PFS3 was 4.2 months (95 % CI,3.6–4.7) and 3.5 months (95 % CI, 3.3–3.6) in the patients with PD-L1 Combined Positive Score (CPS) ≥5 and CPS <5 respectively (P=0.02). The median OS was 17.4 months (95% CI, 17.2–18.1). The multivariate analysis showed that the two parameters were associated with a significantly longer OS: number of metastatic sites <3 and PD-L1 CPS ≥5. Conclusion The patients who received three lines of treatment had a long survival time, and the efficacy of immunotherapy was not affected by the EBV subtypes in advanced GC. The toxicity was managed and the concept of full management needs to be confirmed in the future.